PROSEDUR KERJA PADA ADMINISTRASI FOOD & BEVERAGE PRODUCT KYRIAD HOTEL BUMIMINANG PADANG - Yanti, Mimi Putri (journal of residu, 2019)
This study aims to determine the work procedures for the administration of the food & beverage product Kyriad Hotel Bumi Minang Padang. This type of research is descriptive research with qualitative methods. Data collection techniques used are through interviews, observation and documentation. The data analysis technique used is qualitative data analysis. From the results of the study found several things related to work procedures at the administration of the Kyriad Hotel Bumi Minang Padang food & beverage product, namely: the main work of a food & beverage product admin is often overlooked because it is not only focused on the administration but also helps the operational operational so that the food & beverage product admin often has difficulty ordering goods for operational needs.